A Call to Action. A Critical Review of Mental Health Related Anti-stigma Campaigns - Walsh, Daniel Alexander Benjamin; Foster, Juliet Louise Hallam (Frontiers in Public Health, 2021)
Using a knowledge-attitudes-behavior practice (KABP) paradigm, professionals have focused on educating the public in biomedical explanations of mental illness. Especially in high-income countries, it is now common for education-based campaigns to also include some form of social contact and to be tailored to key groups. However, and despite over 20 years of high-profile national campaigns (e.g., Time to Change in England; Beyond Blue in Australia), examinations suggest that the public continue to Other those with experiences of mental ill-health. Furthermore, evaluations of anti-stigma programs are found to have weak- to no significant long-term effects, and serious concerns have been raised over their possible unintended consequences. Accordingly, this article critically re-engages with the literature. We evidence that there have been systematic issues in problem conceptualization. Namely, the KABP paradigm does not respond to the multiple forms of knowledge embodied in every life, often outside conscious awareness. Furthermore, we highlight how a singular focus on addressing the public's perceived deficits in professionalized forms of knowledge has sustained public practices which divide between “us” and “them.” In addition, we show that practitioners have not fully appreciated the social processes which Other individuals with experiences of mental illness, nor how these processes motivate the public to maintain distance from those perceived to embody this devalued form of social identity. Lastly, we suggest methodological tools which would allow public health professionals to fully explore these identity-related social processes. Whilst some readers may be frustrated by the lack of clear solutions provided in this paper, given the serious unintended consequences of anti-stigma campaigns, we caution against making simplified statements on how to correct public health campaigns. Instead, this review should be seen as a call to action. We hope that by fully exploring these processes, we can develop new interventions rooted in the ways the public make sense of mental health and illness.